DESIGN OF RECTANGULAR-SHAPED MICROSTRIP PATCH ANTENNAS FOR MILLIMETER WAVE BANDS - ABDULLAH, RAWAZ HUSSAIN; AHMED, KAWAN FAIQ (Journal of Duhok University, 2021)
This study presents the design and simulation of two separate rectangular shaped microstrip patch antennas to operate at 38 GHz and 50 GHz millimeter wave (mmWave) bands, using high-frequency structure simulator (HFSS) software package. The work mainly underlines the importance of utilizing a dialectic substrate from ROGRES Corporation. The substrate is used in the design of the proposed antennas, and is made up of hydrocarbon ceramic laminates, known as the RO4350B. The influence of the dielectric material has been studied on the performance of the antennas, like return loss, voltage standing wave ratio (VSWR), antenna bandwidth, antenna gain, and radiation pattern. The obtained 38 GHz antenna has about 8.06 dBi of gain and a 4.01 GHz of bandwidth with a return loss of less than -10dB from 35.23 GHz to 39.24 GHz. On the other hand, the 50 GHz antenna provides a 5.1 dBi of gain with much higher bandwidth (up to 7.2864 GHz) starting from 47.1106 GHz to 54.397 GHz. Beside these remarkable features, the thickness of the selected substrate is 0.762 mm. Both antennas might be used in future 5G wireless communication systems and short-range systems such as machine-to-machine (M2M) and device-to-device (D2D) to fulfill the necessities of wide-bandwidth, high-gain, low-weight, cheap, and easy fabrication.